Improvement of waste water quality by application of mixed algal inocula - Riaz, MA; Ijaz, B; Riaz, A; Amjad, M (Bangladesh Journal of Scientific and Industrial Research, 2018)
Present study aim to investigate application of microalgae for improvement of physiochemical parameters of waste water and improvement of treatment process through reducing the pollutant concentrations including coliform bacteria through their ability to uptake nutrients. Aquatic cultures were conducted in container with dimensions of 1.5×3sq ft. and wastewater samples 5 Litre samples were collected in plastic cans from Sukhnar drain and algal samples were collected from Bhaini Sigyain Village near Ravi Siphon, Lahore. The one experimental treatment lasted for 10 days to make 50% 5 liter water added concentration and 200g of inocula of algae were grown in wastewater container for experiments to optimize at room temperature as local outdoor cultures conditions for wastewater treatment. Total experiment repeated thrice and completed in 30 days. Results show that treatments improved the physiochemical parameter after week. Turbidity (NTU), total suspended solids (mg/L), total dissolved solids (mg/L), nitrate (mg/L), phosphate (mg/L) decrease (P < 0.05) after treatment. However, pH not significantly decreases (P≥ 0.05) pre-treatment values 6.56±0.05 (mg/L) and post-treatment 6.53± 0.057(mg/L). Maximum total coliform disinfection (P < 0.05) was indicated with 200 g of algae was pre-treatment 1602± 6.8 (MPN) and post treatment 1447±39.5 (MPN) observed. Bangladesh J. Sci. Ind. Res.53(1), 77-82, 2018